2018
DOI: 10.1186/s40779-018-0166-5
|View full text |Cite
|
Sign up to set email alerts
|

Infectious diseases during the European Union training mission Mali (EUTM MLI) – a four-year experience

Abstract: BackgroundThe European Union Training Mission Mali (EUTM MLI) is a multinational military training deployment to the Western African tropical nation of Mali. Based on routinely collected disease and non-battle injury surveillance data, this study quantifies the true impact of infectious diseases for this tropical mission and potential seasonal variations in infectious disease threats.MethodsCategorized health events during the EUTM MLI mission and associated lost working days were reported using the EpiNATO-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Interestingly, there seem to be seasonal trends in the epidemiology of cyclosporiasis, although they have been inconsistently reported over different geographic regions [2,6]. As known from other reports, fecal-oral infections are particularly frequent in the moist hot weather of the rainy seasons in the tropics [27]. Cyclosporiasis is no exemption with peaks in the rainy season or in the summer [7].…”
Section: Introductionmentioning
confidence: 95%
“…Interestingly, there seem to be seasonal trends in the epidemiology of cyclosporiasis, although they have been inconsistently reported over different geographic regions [2,6]. As known from other reports, fecal-oral infections are particularly frequent in the moist hot weather of the rainy seasons in the tropics [27]. Cyclosporiasis is no exemption with peaks in the rainy season or in the summer [7].…”
Section: Introductionmentioning
confidence: 95%
“…Frickmann et al [ 342 ] analysed the infectious diseases for which military personnel who took part in the European Union Training Mission in Mali (EUTM Mali) sought medical care from 2013 to 2017. The total number of medical consultations was 9,805.…”
Section: Anthrax In Warmentioning
confidence: 99%
“…This collects a diagnosis for each presentation to a medical treatment facility and is submitted every week. Recently, this has been used in the EU mission in Mali39 to determine the burden of communicable disease in a high-risk environment. The monitoring demonstrated that the majority of disease was, in fact, relatively minor respiratory and gastrointestinal infectious disease.…”
Section: Monitoringmentioning
confidence: 99%